Pengaruh Pembiayaan Mudharabah dan Musyarakah terhadap Profitabilitas (ROA) pada Bank Muamalat Indonesia Periode 2017-2019 - Sri Wellis Anggraeni; Wirman Wirman (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2022)
The purpose of this study is to determine the effect of mudharabah and musyarakah financing on profitability (ROA) at Bank Muamalat Indonesia for the 2017-2019 period. The method used is a quantitative method with secondary data types. The sampling technique used was saturated sampling. The population as well as the sample used is the monthly financial report of Bank Muamalat Indonesia with a total of 36 data. Data collection techniques using library research and documentation techniques. The tests in this study include the classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination (R2) testing with the help of a data processing program in the form of SPSS version 16. The results of this study are partially mudharabah financing has a significant negative effect on profitability (ROA). ) and musyarakah financing have a significant positive effect on profitability (ROA). Meanwhile, mudharabah and musyarakah financing simultaneously have a significant positive effect on profitability (ROA).